Racial variations in sciatic nerve anatomy: A systematic review and meta-analysis - Seid Mohammed Abdu; Hussen Abdu; Endris Seid Muhaba; Ebrahim Msaye Assefa; Gosa Mankelkl (PLoS ONE, 2026)
Background The sciatic nerve (SN), the longest and largest nerve in the body, arises from the L4-S3 nerve roots and exits as a single trunk below the piriformis muscle through the greater sciatic foramen. However, variations in its anatomy are common, believed to originate from embryological development. These variations show significant racial and geographical differences, which have often been overlooked in previous review studies. Therefore, this meta-analysis aims to address this gap by systematically reviewing global data to evaluate the impact of race on sciatic nerve variations. Methods A systematic review and meta-analysis were conducted to assess the pooled prevalence of SN variations among racial subgroups. A comprehensive literature search was performed using PubMed, Google Scholar, Hinari, and additional sources, including major anatomical journals and cross-referenced articles. Subgroup analyses by region and country were also conducted using a random-effects model. Heterogeneity was assessed with the Cochrane Q test and the I² statistic. Results Type A, considered the normal pattern, had the highest pooled prevalence at 86%. The remaining 14% represented variations of the sciatic nerve (SN). Among these, Type B was the most common at 7%, followed by Type C and G each observed in 2% of limbs, while less frequent variations included Type Type D (1%), Type E (0%), and Type F (0% (0–1)). Racial analysis showed that SN variations occurred in 15% of Asians, 12% of Whites, and 13% of Blacks. Regarding continents, the highest prevalence was in Asia with 15%, the second highest prevalence was observed in Europe with 14%, followed by Africa with 13%, and the lowest in America with 11%. No significant differences were found among the races and continents. However, East Asia showed the highest significant prevalence, with China at 35% and Japan at 32%. Conclusion This review revealed only modest and statistically non-significant differences in the prevalence of sciatic nerve variations across broad racial and continental groups. In contrast, substantial variation was observed at the regional level, with particularly high prevalence rates in East Asian countries, specifically China and Japan. These findings suggest that regional factors contribute more to the observed variations than racial factors.